FRI0071 Predictors for The Development of anti-Citrullinated Protein Antibodies in Individuals Genetically at Risk for Rheumatoid Arthritis. (15th July 2016) - Alpizar-Rodriguez, D.; Brulhart, L.; Müller, R.; Möller, B.; Dudler, J.; Ciurea, A.; Walker, U.; Von Mühlenen, I.; Kyburz, D.; Zufferey, P.; Mahler, M.; Bas, S.; et al.
Abstract : Background: In genetically susceptible individuals, environmental factors induce a pathological activation of the immune system that may eventually lead to systemic autoimmunity and subsequent clinical manifestations. Different risk factors may be relevant for the development of this systemic autoimmunity, representing one of the phases preceding the onset of rheumatoid arthritis (RA) (1). Objectives: To identify predictors for the development of systemic autoimmunity associated with RA in individuals genetically at increased risk. Methods: This is an ongoing prospective cohort study of individuals at increased risk of developing RA, namely first degree relatives of patients with autoimmune diseases (FDRs). Individuals without clinical evidence of RA were enrolled and followed-up yearly. We included all individuals with available anti-citrullinated protein antibodies (ACPA) status (anti-CCP 2, 3.0, or 3.1). We used logistic regression to analyze univariable and multivariable associations between ACPA positivity and putative risk factors or symptoms, including the Connective Tissue Disease Screening Questionnaire (CSQ), 3 or more positive responses represented possible RA (2). Results: A total of 1064 of FDRs were analyzed, of which 57 (5%) were ACPA-positive. FDRs had a median age of 45 (interquartile range (IQR): 34–56) years, 76% were female, 25% had at least one self-reported episode of joint swelling, however on examination only 12% had ≥1 swollen joint (Table 1 ). In univariable analyses, ACPA-positivity was associated with older age, female sex, tender joints (self reported, ≥1 on examination and mean count), mean swollen joint count, CSQ score and self-reported symptoms associated with possible RA by CSQ. Other variables such as tobacco smoking, alcohol consumption, obesity or tooth loss were not significantly associated with ACPA status. In women, ACPA-positivity was significantly associated with age (OR: 1.1, 95%CI: 1.0–1.1), but not in men (OR: 1.0, 95%CI: 0.9–1.1). In the multivariable adjusted analysis, older age and self-reported symptoms associated with possible RA by CSQ remained independently associated with ACPA positivity. Female sex and tobacco smoking ever had a strong but not significant association. Conclusions: In individuals at high risk for RA, the development of ACPAs was associated with older age and self-reported symptoms related with possible RA. We found a trend for an association between female sex and tobacco smoking with ACPA positivity, which did however not reach statistical significance. These findings suggest similar risk factors for the development of ACPAs and for classifiable RA, suggesting that the development of ACPAs is a valid proxy for RA development. References: Gerlag DM et al. Ann Rheum Dis. 2012; 71(5): 638–41. Karlson EW, et al. Ann Epidemiol 1995;5:297–302. Disclosure of Interest: None declared